2008
DOI: 10.1080/14622200802443742
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for treatment failure in smokers: Relationship to alcohol use and to lifetime history of an alcohol use disorder

Abstract: Little is known about the impact of alcohol involvement on smoking cessation relapse or possible mechanisms for these associations. We addressed these issues using data from a randomized clinical trial of 2 types of framed messages (gain vs. loss) in conjunction with open label sustained-release (SR) bupropion (Toll et al., 2007) (N = 249). Participants were categorized according to whether or not they were diagnosed with a lifetime alcohol use disorder (AUD; i.e., current or past alcohol abuse or past alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 52 publications
5
75
0
1
Order By: Relevance
“…The failure to find a clear association between attempts to stop smoking and attempts to reduce alcohol consumption goes against individual‐level findings in the literature 13, 14, 15. This may be because of low statistical power, with the samples in this analysis limited to smokers and high‐risk drinkers which comprises less than one‐fifth of the sample.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The failure to find a clear association between attempts to stop smoking and attempts to reduce alcohol consumption goes against individual‐level findings in the literature 13, 14, 15. This may be because of low statistical power, with the samples in this analysis limited to smokers and high‐risk drinkers which comprises less than one‐fifth of the sample.…”
Section: Discussionmentioning
confidence: 69%
“…Attempts to quit smoking are less successful among those with alcohol use disorder 13, 14, 15 and episodes of alcohol consumption during a smoking cessation attempt are associated with a greater risk of relapse to smoking 16. Several mechanisms may contribute to the association between alcohol and tobacco use, including genes involved in regulating neurotransmitters, cross‐tolerance and cross‐sensitization to both drugs, conditioning mechanisms in which cravings for alcohol or nicotine are elicited by similar environmental cues, and common psychological and social factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Smokers attempting to quit report higher craving for cigarettes (Delfino, Jamner, & Whalen, 2001;Piasecki, McCarthy, Fiore, & Baker, 2008;Piasecki et al, 2011) and are significantly more likely to lapse after they consume alcohol (Brandon et al, 1990;Kahler et al, 2010;Leeman et al, 2008;Shiffman et al, 1996b;van Zundert et al, 2012). Furthermore, smokers who drink more after they quit smoking are significantly less likely than those who drink less to maintain long-term smoking abstinence (Hyland et al, 2004;McClure, Wetter, deMoor, Cinciripini, & Gritz, 2002).…”
Section: Introductionmentioning
confidence: 91%
“…Unfortunately, almost all unaided quitters (95%) resume regular smoking (Hughes, Keely, & Naud, 2006), and relapse is frequently preceded by isolated incidents of cigarette smoking known as lapses (Kenford et al, 1994). Three specific high-risk triggers-alcohol consumption (Brandon, Tiffany, Obremski, & Baker, 1990;Kahler, Spillane, & Metrik, 2010;Leeman et al, 2008;Shiffman, Paty, Gnys, Kassel, & Hickcox, 1996b;van Zundert, Kuntsche, & Engels, 2012), presence of others smoking (Shiffman, 1982;Shiffman et al, 1996b;Solomon et al, 2007), and negative affect (Kenford et al, 2002;Niaura et al, 2001;Shiffman et al, 1996b)-have consistently been identified as critical postcessation precipitants of lapse/relapse. However, exceedingly few data have addressed how these triggers combine to impact cessation outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous research (e.g., Benowitz et al, 2002), studies about smokers from clinical population should include multiple assessments (baseline, post-treatment and follow-ups), and biochemical verification to avoid an overestimation of the absolute abstinence rate. The aim of the present study was to analyze the influence of 30 specific facets of the Five-Factor Model of personality on the short and long-term outcomes of a smoking cessation treatment.…”
Section: Introductionmentioning
confidence: 99%